Instrumental responses and Pavlovian stimuli as temporal referents in a peak procedure. Issue 2 (February 2023) - Burgess, Katy V; Honey, Robert C; Dwyer, Dominic M
Three experiments investigated whether the nature of the temporal referent affects timing behaviour in rats. We used a peak procedure and assessed timing of food well activity as a function of whether the referent was an instrumental response (a lever press that resulted in the withdrawal of the lever) or a conditioned stimulus (CS) that was 2 s in Experiment 1, 500 ms in Experiment 2, and 800 ms in Experiment 3. In all experiments, the interval between the offset of the temporal referent and food was 5 s. The curve fits for each experiment revealed no differences in peak time, but magazine responding immediately following the CS was higher than following a lever press. This pattern of results was interpreted as reflecting a combination of (a) ambiguity in which component of the 500 ms–2-s auditory stimulus was serving as the referent and (b) response competition between lever pressing and magazine activity. Critically, these results suggest that peak timing in rats is unaffected by whether a lever press or CS serves as the referent. This conclusion is consistent with theoretical models of timing behaviour, but not with evidence from humans showing that the subjective perception of time is affected by whether the cause of an outcome was self-generated or not.